Correlation of adsorbed and embedded palladium species in chitosan composite nanofibers with their catalytic activities for Suzuki reactions. (September 2022) - Su, Baogang; Zhang, Qi; Shao, Linjun; Zhou, Shujing; Li, Jinjing; Du, Yijun; Qi, Chenze
Abstract: Heterogeneous palladium catalysts play an important role in the synthetic organic chemistry. Palladium species have been adsorbed on the surface of solid matrices or embedded inside solid matrices to prepare recyclable heterogeneous catalysts. Due to the different surrounding environment, these two type palladium species had different electronic properties and catalytic performances. In this study, we fabricated three series of chitosan composite nanofibers with adsorbed and embedded palladium species. Their fiber morphologies and chemical structures were characterized by SEM and FT-IR, respectively. Positron annihilation lifetime spectra (PALS) showed that the intensities (I3 ) of o -Ps annihilations were all linearly decreased with the increase of palladium contents in the chitosan composite nanofibers. Moreover, compared with the palladium adsorbed chitosan composite nanofibers, the palladium embedded chitosan composite nanofibers had stronger o -Ps annihilation ability, which could be ascribed to the stronger electron donating property of embedded palladium species and higher crosslinking of chitosan molecules by embedded palladium species. At last, the I3 values were successfully correlated with the rate constants of chitosan supported palladium composite nanofibers catalyzed Suzuki reactions of iodobenzene with phenylboric acid. Therefore, we have developed a facile method to distinguish the adsorbed and embedded palladium species by PALS, which can be further related with their catalytic performance. Highlights: PdCl2 absorbed and embedded chitosan composite nanofibers were prepared. The absorbed and embedded PdCl2 had different o-Ps annihilation and activity. The intensities (I3 ) of o-Ps annihilation were correlated with the amount of PdCl2. The I3 values were linearly correlated with the reaction rate constants.